Synthesis of 2-Aryl-3-(arylselanyl)imidazo[1,2-a]pyridines: Copper-Catalyzed One-Pot, Two-Step Se-Arylation of Selenium with Imidazopyridines and Triarylbismuthanes - Kondo, Kaito; Matsumura, Mio; Kanasaki, Keiko; Murata, Yuki; Kakusawa, Naoki; Yasuike, Shuji (Synthesis, 2018)
A simple and general method for the synthesis of 2-aryl-3-(arylselanyl)imidazo[1,2-a]pyridines is described. A one-pot, two-step reaction between triarylbismuthanes and diimidazopyridyl diselenides, generated from imidazo[1,2-a]pyridines and Se powder in the presence of CuI and 1,10-phenanthroline, affords 3-selanylimidazopyridines in moderate to excellent yields under aerobic conditions. The reactions proceed efficiently and the selenium and all the aryl groups on bismuth are transferred to the coupling products. Triarylbismuthanes give better results compared to other aryl donors containing elements such as boron, silicon, tin, and iodine.
Keywords: imidazo[1,2-a]pyridines; selenium; triarylbismuthanes; copper catalyst; one-pot, two-step reaction